The Best Chance For All : A Policy Roadmap for Post-Pandemic Panic. - Kift, Sally; Zacharias, Nadine; Brett, Matt (Student Success v.12 n.3 p.26-36 https://doi.org/10.5204/ssj.1782, 2021)
'The Best Chance for All' was developed in 2018 as a long-term policy vision for student equity in Australian tertiary education. We argue in this article that COVID-19 has exacerbated the issues that the policy vision sought to address and has increased demands on and of post-secondary education. Specifically, we argue that the magnitude of the social and economic challenges presented by COVID-19 warrants holistic policy responses that enable the transition to a connected tertiary education system; one designed to deliver choice and flexibility for lifelong learners. A roadmap for this transition exists in the form of 'The Best Chance For All'. The vision can be actuated through demand driven funding arrangements across tertiary education that are coherently aligned to optimise the performance of both the higher and vocational education sectors and are underpinned by sustained investment in equity outreach and support. [Author abstract]